1992
DOI: 10.1126/science.257.5072.954
|View full text |Cite
|
Sign up to set email alerts
|

Coeval 40 Ar/ 39 Ar Ages of 65.0 Million Years Ago from Chicxulub Crater Melt Rock and Cretaceous-Tertiary Boundary Tektites

Abstract: (40)Ar/(39)Ar dating of drill core samples of a glassy melt rock recovered from beneath a massive impact breccia contained within the 180-kilometer subsurface Chicxulub crater in Yucatán, Mexico, has yielded well-behaved incremental heating spectra with a mean plateau age of 64.98 +/- 0.05 million years ago (Ma). The glassy melt rock of andesitic composition was obtained from core 9 (1390 to 1393 meters) in the Chicxulub 1 well. The age of the melt rock is virtually indistinguishable from (40)Ar/(39)Ar ages ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(133 citation statements)
references
References 23 publications
9
122
0
2
Order By: Relevance
“…It was also shown that the thickness of the K/T boundary impact ejecta in the North American region decreased with distance, as one would expect if it had been ejected from the Chicxulub structure (Hildebrand and Stansberry 1992;Vickery et al 1992). The measured age of the Chicxulub melt rock (64.98 ± 0.05 Ma and 65.2 ± 0.4 Ma) was found to be the same as that of impact melt spherules (65.01 ± 0.08 Ma) deposited in a K/T boundary unit in Haiti (Swisher et al 1992;Sharpton et al 1992). The strontium and oxygen isotopic compositions of impact melt spherules in K/ T boundary sediments in Haiti were found to be consistent with a mixture of the Chicxulub melt rock and a K/T marine carbonate (Blum and Chamberlain 1992;Blum et al 1993).…”
Section: The Chicxulub Impact Cratermentioning
confidence: 69%
“…It was also shown that the thickness of the K/T boundary impact ejecta in the North American region decreased with distance, as one would expect if it had been ejected from the Chicxulub structure (Hildebrand and Stansberry 1992;Vickery et al 1992). The measured age of the Chicxulub melt rock (64.98 ± 0.05 Ma and 65.2 ± 0.4 Ma) was found to be the same as that of impact melt spherules (65.01 ± 0.08 Ma) deposited in a K/T boundary unit in Haiti (Swisher et al 1992;Sharpton et al 1992). The strontium and oxygen isotopic compositions of impact melt spherules in K/ T boundary sediments in Haiti were found to be consistent with a mixture of the Chicxulub melt rock and a K/T marine carbonate (Blum and Chamberlain 1992;Blum et al 1993).…”
Section: The Chicxulub Impact Cratermentioning
confidence: 69%
“…The authors then recalculated the K-Pg boundary age values proposed by SWISHER et al (1992SWISHER et al ( , 1993 and IZETT et al (1991). The new figures are:…”
Section: Integrated Radiometric and Astronomical Datingmentioning
confidence: 99%
“…In the nineties, the K-Pg boundary was generally given a value of 65.0 Ma (SWISHER et al, 1992(SWISHER et al, , 1993DALRYMPLE et al, 1993;GRAD-STEIN et al, 1994;CANDE & KENT, 1995;BERG-GREN et al, 1995;GRADSTEIN & OGG, 1996).…”
Section: Radiometric Datingmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of this extinction has been widely studied and debated (Alvarez et al, 1980;Alvarez et al, 1982;Smith and Hertogen, 1980;Hsüv, 1980;Kyte et al, 1980;Wolbach et al, 1985;Rampino and Reynolds, 1983;Officer and Drake, 1983;Officer and Drake, 1985;Officer et al, 1987;Snee 1991). Impact by a large extraterrestrial bolide (Alvarez et al, 1980;Alvarez et al, 1982;Smith and Hertogen, 1980;Hsüv, 1980;Kyte et al, 1980;Izett et al, 1991;Marin et al, 1992;Swisher et al, 1992) and widespread Deccan volcanoes eruption in western India during the same geological slot (Rampino and Reynolds, 1983;Officer and Drake, 1983;Officer and Drake, 1985;Officer et al, 1987;Hoffman et al, 2000), are two major possibilities on which scientists have focused their studies. Each of these two was capable to create conditions for large scale extinction of living species and hence supplementary evidences from the sedimentary rocks; both geochemical and paleontological are important to distinguish between the two possibilities.…”
Section: Introductionmentioning
confidence: 99%